2022
DOI: 10.3390/foods11020206
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Hydrothermal Processing to Align Structure and In Vitro Digestion Kinetics between Three Different Pulse Types

Abstract: Processing results in the transformation of pulses’ structural architecture. Consequently, digestion is anticipated to emerge from the combined effect of intrinsic (matrix-dependent) and extrinsic (processed-induced) factors. In this work, we aimed to investigate the interrelated effect of intrinsic and extrinsic factors on pulses’ structural architecture and resulting digestive consequences. Three commercially relevant pulses (chickpea, pea, black bean) were selected based on reported differences in macronutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 73 publications
8
17
0
Order By: Relevance
“…Around 92-96% of all starch was hydrolyzed after 2h of small intestinal phase (Figure 2D, Table 3). This is line with previous research on diverse pulse types (Edwards et al, 2020;Gwala, Pallares Pallares, Pälchen, Hendrickx, & Grauwet, 2020;Pälchen et al, 2022).…”
Section: From a Conventional To Automated In Vitro Static Digestion A...supporting
confidence: 93%
See 2 more Smart Citations
“…Around 92-96% of all starch was hydrolyzed after 2h of small intestinal phase (Figure 2D, Table 3). This is line with previous research on diverse pulse types (Edwards et al, 2020;Gwala, Pallares Pallares, Pälchen, Hendrickx, & Grauwet, 2020;Pälchen et al, 2022).…”
Section: From a Conventional To Automated In Vitro Static Digestion A...supporting
confidence: 93%
“…A starch hydrolysis of 81-93% was reached after 2h of small intestinal digestion. This is again in line with previous static studies on diverse pulse types (Edwards, Maillot, Parker, & Warren, 2018;Gwala et al, 2020;Pälchen et al, 2022;Rovalino-Córdova, Fogliano, & Capuano, 2019).…”
Section: Semi-dynamic Digestion Kinetics Of a Cooked Lentil Samplesupporting
confidence: 92%
See 1 more Smart Citation
“…Applying a kinetic approach, in vitro studies focusing on lipid digestion elucidated the effect of emulsion stability on lipid digestion (Verkempinck, Salvia-Trujillo, Moens, Charleer, et al, 2018), and even postulated a plausible reaction mechanism for lipolysis (Infantes-Garcia et al, 2021). In the field of macronutrient digestion in pulses, a strong relation between thermal processing time, food structure (hardness), cell wall properties, and starch and protein digestion kinetics could be established (Duijsens et al, 2021;Pälchen et al, 2022).…”
Section: Why Consider a Kinetic Approach?mentioning
confidence: 99%
“…Most commonly, since individual cotyledon cells can be considered a representative fraction of disintegrated cooked pulse seeds, isolated cotyledon cells (ICC) are considered [20][21][22][23][24][25][26][27][28][29][30]. Since this approach entails the omission of certain fractions (such as cell clusters, fiber-rich seed coat material, and ruptured cells), it can be considered a reductionist approach [30,31]. The study of ICC fractions revealed a positive correlation between the applied cooking time and the starch and protein digestion rate and extent of isolated of black beans, common beans (Phaseolus vulgaris), and Bambara groundnut (Vigna subterranea) [31][32][33].…”
Section: Introductionmentioning
confidence: 99%